2020
DOI: 10.3390/molecules25030726
|View full text |Cite
|
Sign up to set email alerts
|

Quality Enhancement Mechanism of Alkali-Free Chinese Northern Steamed Bread by Sourdough Acidification

Abstract: Alkali was used to adjust the pH and neutralize the excess acids of dough in the processing of Chinese northern steamed bread (CNSB). However, extra alkali addition generally resulted in alkalic flavor and poor appearance. The aim of this work was to investigate the role of proofed dough pH on the texture of CNSB. Correlation analysis demonstrated that the pH value of proofed dough has a significant effect on the textural properties of CNSB. The mechanism studies found that gradual acidification of dough by la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…32 Stepwise canonical discriminant analysis was used to discriminate the geographical origins of steamed breads fermented with different traditional starters according to their aroma compounds. 28,29 Sensory evaluation of steamed bread The cooled steamed breads were placed on separate white porcelain plates, coded with three randomized letters, before presenting to 20 trained sensory panelists (10 male and 10 female, aged [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] in individual sensory rooms at 25 ± 1 °C with natural daylight. They were evaluated according to the criteria in Supporting Information Table S1.…”
Section: Quality Analysis Of Steamed Breadmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Stepwise canonical discriminant analysis was used to discriminate the geographical origins of steamed breads fermented with different traditional starters according to their aroma compounds. 28,29 Sensory evaluation of steamed bread The cooled steamed breads were placed on separate white porcelain plates, coded with three randomized letters, before presenting to 20 trained sensory panelists (10 male and 10 female, aged [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] in individual sensory rooms at 25 ± 1 °C with natural daylight. They were evaluated according to the criteria in Supporting Information Table S1.…”
Section: Quality Analysis Of Steamed Breadmentioning
confidence: 99%
“…[20][21][22] Potato steamed bread fermented with traditional starter from Inner Mongolia showed lower specific volume than that from Shandong Province; however, it had a higher height/diameter ratio, with variation in sensory qualities, depending on the origin of the starters. 6,20 Much research has studied the quality of steamed bread and its influencing factors, such as starters and chemical components, 8,10,19,[21][22][23][24] but correlation among microbiota, aroma compounds and qualities of steamed bread is still lacking and should be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of free sulfhydryl groups reflects the changes in disulfide bonds, and there is a close relationship between disulfide bond amounts and gluten protein structures, which determines protein aggregation and maintains the stability of the protein matrix (Wang et al, 2014a). Yan et al (2020) found that during the fermentation and cooking process of steamed bread, heating led to formation of disulfide bonds, and heatinduced protein denaturation exposed buried SH, resulting in in-SH being more easily oxidized and exchanged between SH and S-S, thus forming S-S between protein molecules and contributing to the structure of steamed bread. The free SH contents increased with decreasing pH.…”
Section: Thiol and Disulfide Bond Contentmentioning
confidence: 99%
“…Compared with native flour, LOF-5, LOF-30, and HOF-5 showed increase in dough stability time [15], which might be due to the mild ozonation of glutenin. However, the decrease of pH might affect the fermentation process of the wheat dough and do harmful effect to the quality of steamed bread [30]. For HOF-30, the great decrease of pH reduced the stability of dough during mixing and might also affect the later fermentation process [15,19], thus leading to the great decrease of specific volume and increase of hardness in steamed bread.…”
Section: Specific Volume Texture and Inner Structure Of Steamedmentioning
confidence: 99%